Espectroscopia vibracional e cálculos de primeiros princípios no cristal de 2'deoxyadenosina monohidratada e propriedades vibracionais sob altas pressões - Quimbayo, Jennyffer Stefania Martinez (2019)
Nucleotides and nucleosides are DNA-forming molecules that can be crystallized and analyzed to know their vibrational and structural characteristics. In this work we present computational simulations with first principle calculations to determine the vibrational properties of deoxyadenosine monohydrate crystal and results of vibrational spectroscopy under ambient conditions. X-ray diffraction analysis confirmed the crystal structure. The computational results were in good agreement with the Raman and infrared spectroscopy experiments, which allowed the identification of most normal vibration modes. The meassurements of Raman spectroscopy under high pressure were perfomed using a diamond anvil cell. From this study there was evidence of the occurrence of two phase transitions, one around 0.8 GPa and the second between 2.3 and 2.9 GPa. Changes in Raman spectra still suggest a possible conformational change between 3.7 and 3.9 GPa. Finally, it is suggested to complement hydrogen bonding modes with low wavelength modes.